Clinical Subtypes of Medication Overuse Headache – Findings From a Large Cohort. Issue 9 (3rd October 2019) - Viana, Michele; De Icco, Roberto; Allena, Marta; Sances, Grazia; Højland, Jensen Rigmor; Katsarava, Zaza; Lainez, Miguel J. A.; Fadic, Ricardo; Goicochea, Maria Teresa; Nappi, Giuseppe; Tassorelli, Cristina; ,
Abstract : Background: The International Classification of Headache Disorders lists different subtypes of medication overuse headache (MOH), according to the medication overused. The aim of this study is to evaluate whether the different subtypes correspond to clinically distinguishable phenotypes in a large population. Method: This descriptive cross‐sectional observational study included 660 patients with MOH referred to headache centers in Europe and Latin America as a part of the COMOESTAS project. Information about clinical features was collected with structured patient interviews and with self‐administered questionnaires for measuring disability, anxiety, and depression. Results: Female/male ratio, body mass index, marital status, and level of education were similar among in subjects enrolled in the 5 centers. The mean age was higher among subjects overusing triptans (T‐MOH) with respect to subjects overusing simple analgesic (A‐MOH). Duration of headache before chronification was longer in T‐MOH (19.2 ± 11.9 years) and in subjects overusing ergotamines (E‐MOH, 17.8 ± 11.7 years) with respect to the A‐MOH group (13.1 ± 10.9; P  < .001 and P  = .017, respectively) and in T‐MOH with respect multiple drug classes (M‐MOH, 14.9 ± 11.7; P  = .030). Migraine Disability Assessment (MIDAS) score was significantly lower in E‐MOH group (33.6 ± 41.6), while T‐MOH group (56.8 ± 40.6) had a significant lower MIDAS score with respect to M‐MOH (67.2 ± 62.5; P  = .016 and P  = .037, respectively). Prevalence of depression and anxiety was lower in patients overusing T with respect to other groups of patients ( χ 2  = 10.953, P  = .027 and χ 2  = 25.725, P  < .001, respectively). Conclusion: In this study on a large and very well characterized population of MOH, we describe the distinctive clinical characteristics of MOH subtypes. These findings contribute to more clearly define the clinical picture of a poorly delineated headache disorder. They also provide some insights in the possible trajectories leading to this highly disabling chronic headache, that is classified as a secondary form, but whose occurrence is entirely dependent on an underlying primary headache.